Exosomes as a novel cell‐free therapeutic approach in gastrointestinal diseases. Issue 7 (7th December 2018) - Baghaei, Kaveh; Tokhanbigli, Samaneh; Asadzadeh, Hamid; Nmaki, Saeed; Reza Zali, Mohammad; Hashemi, Seyed Mahmoud
Abstract: Cell communication through extracellular vesicles (EVs) has been defined for many years and it is not limited only to neighboring cells, but also distant ones in organisms receive these signals. These vesicles are secreted from the variety of cells and are composed of a distinctive component such as proteins, lipids, and nucleic acids. EVs have different classified subgroups regarding their cell origin, in this context, exosomes are the most appealing particles in cell biology, especially clinical in recent years and are represented as novel therapeutic agents with numerous advantages alongside and/or over cell therapy. However, cell therapy had a hopeful outcome in gastrointestinal diseases which have minimal alternatives in their treatments. Inflammatory bowel disease (IBD), liver fibrosis, gastrointestinal cancers are the examples that cell therapy and immunotherapy were applied in their treatment, therefore, the cell products like exosomes are the beneficial option in their treatment even cancers with promising results in animal models. In this review, we consider the main defined biogenesis, function, and component of secreted exosomes in different cells with a specific focus on the potential application of these exosomes as a cell‐free therapeutic approach in gastrointestinal diseases like IBD, gastric cancer, and colon cancer. Additionally, exosomes role as therapeutic reagents mainly mesenchymal stem cells and dendritic cell‐derived exosomes in different studies have been under intense investigation and even they are being studied in different clinical trials. Therefore, all these striking functions described for secretome implies the importance of these biocarriers. Abstract : In this review, we consider the main defined biogenesis, function and component of secreted exosomes in different cells with a specific focus on the potential application of these exosomes as a cell‐free therapeutic approach in gastrointestinal diseases.